Effect of non-uniform reactor cooling on fracture and constraint of a reactor pressure vessel - Qian, Guian; Niffenegger, Markus; Sharabi, Medhat; Lafferty, Nathan (Wiley, 2018)
In the lifetime prediction and extension of a nuclear power plant, a reactor pressure vessel (RPV) has to demonstrate the exclusion of brittle fracture. This paper aims to apply fracture mechanics to analyse the non‐uniform cooling effect in case of a loss‐of‐coolant accident on the RPV integrity.